The Arabidopsis transcription factor NAI1 is required for enhancing the active histone mark but not for removing the repressive mark on PYK10, a seedling–specific gene upon embryonic-to-postgerminative developmental phase transition - Yoshii, Masakatsu (Plant Signal Behav, 2015)
We have recently shown that the expression onset of a seedling-specific gene, PYK10, occurs in a cell-by-cell manner upon the transition from the embryonic to the postgerminative phase and during embryogenesis in seed maturation regulator mutants such as lec1, and implicated epigenetic mechanisms in the process. Here, the role of the NAI1 transcription factor required for PYK10 expression in the developmental switching of PYK10 was investigated. The cell-by-cell onset of PYK10-EGFP in lec1 embryo was still observed in the nai1 background, but at greatly reduced levels. Decreases in the level of the repressive histone mark, H3K27 trimethylation observed upon the transition to the postgeminative phase normally occurred in nai1. However, concomitant increases in the level of the active mark, H3K4 trimethylation observed in wild type was significantly compromised in nai1. These results indicate that the switching of PYK10 upon developmental phase transition involves 2 separable steps of chromatin state change.